Konsep Kurikulum Terpadu Perspektif Pendidikan Islam - Novianti, Heni (Jurnal Penelitian Pendidikan Islam, 2019)
In an Islamic educational institution, the curriculum is considered as the core of the teaching rules. Within its limits and its development has a major role to improve the value of education and teaching. Integrated curriculum in Islamic education is learning to form a unity. The output of this integrated curriculum is to prepare future humans with character, noble character, wide-minded, intelligent, and skilled. This study aims to explore the concept of an integrated curriculum in the perspective of Islamic education. This study uses the literature study method. The results of the study show that an integrated curriculum is the only choice in the practice of Islamic education, so that the educational process is not partial, but whole, comprehensive, and integrative.